Economic Valuation of Sun Bear (Helarctos malayanus) and Sumatran Elephant (Elephas maximus sumatranus) Based on Maintenance Cost Approach - Audelia Thalita Ramadhanti; Yanto Santosa; Arzyana Sunkar (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Sun bear (Helarctos malayanus) and sumatran elephant (Elephas maximus sumatranus) are two species with high population decline due to poaching and illegal wildlife trade. It is still difficult to enforce laws related to hunting and wildlife trade due to legal standardization that can be used as an economic basis for lawsuits. One method of quantifying the economic value of animals can be done through an economic valuation process. This study aims to examine the economic value of sun bears and sumatran elephants based on a maintenance cost approach. The research was conducted at the conservation institutions of Medan Zoo, Siantar Zoo, and PPS Tashikoki from February – May 2021. The method used in the study was to manage conservation institutions to obtain the amount of cost allocation for animal care that refers to the five principles of animal welfare. The results showed that the sun bear's economic value based on its maintenance cost for 2 years reached Rp. 76,760,000 and for the sumatran elephant, it reached Rp. 621,730,000. The highest maintenance cost allocation for these two species is in the feed allocation. This high economic value indicates a disproportionate amount of fines given to the perpetrators of hunting and illegal wildlife trade, which has implications for weak legal products and does not cause a deterrent effect.